Modification of lignin properties using alpha particles and gamma-rays for diverse applications. (January 2023) - Kumar, Ashish; Kumar, G. Anil
Abstract: The irradiation of lignocellulosic biomass using high-energy radiations provides an economical green alternative method over chemical methods for the pretreatment of biomass before its use for applications like the production of biofuels, new sustainable materials, and filler for polymer composites. Thus, irradiation of lignin using high-energy ionizing radiations has potential use in lignin-based biorefineries and bio-polymer industries. In the present work, the kraft lignin was subjected to gamma-rays (1.17 and 1.33 MeV) up to a dose of 200 kGy, and alpha radiations (5.2 MeV) up to a dose of 1200 mGy. The irradiation produces free radicals in the irradiated material, triggering chemical reactions and changing the lignin's physicochemical properties. The chemical and structural changes in the irradiated lignin with different radiation doses were analyzed with various characterization techniques such as FTIR, XRD, DSC, and TGA. The results showed that gamma-rays significantly affected the amorphous regions of lignin samples compared to their crystalline regions. In contrast, alpha particles irradiation of lignin remarkably affected the crystalline structural morphology compared to the amorphous phase. The effect of gamma-rays irradiation on amorphous regions of lignin was more pronounced at low irradiation doses than at high doses. The impact of alpha particles irradiation on the physicochemical properties of lignin was studied and reported for the first time. The present work helps to choose the appropriate type of nuclear radiation for the pretreatment process as per the applications. Highlights: The influence of gamma rays and alpha rays on the properties of lignin is studied. The gamma irradiation assists the thermal-depolymerization process of lignin. Pretreatment of lignin by gamma-rays increases the compatibility of the lignin. Alpha rays can be employed for the pretreatment of lignocellulosic biomass.